Removal of bisphenol A from aqueous media using a highly selective adsorbent of hybridization cyclodextrin with magnetic molecularly imprinted polymer - Mamman, S.; Suah, F. B. M.; Raaov, M.; Mehamod, F. S.; Asman, S.; M. Zain, N. N. (The Royal Society, 2021)
In this study, a unique magnetic molecularly imprinted polymer (MMIP) adsorbent towards bisphenol A (BPA) as a template molecule was developed by bulk polymerization using β-cyclodextrin (β-CD) as a co-monomer with methacrylic acid (MAA) to form MMIP MAA–βCD as a new adsorbent. β-CD was hybridized with MAA to obtain water-compactible imprinting sites for the effective removal of BPA from aqueous samples. Benzoyl peroxide and trimethylolpropane trimethacrylate were used as the initiator and cross-linker, respectively. The adsorbents were characterized by Fourier transform infrared spectroscopy, scanning electronic microscopy, transmission electron microscopy, vibrating sample magnetometer, Brunauer–Emmett–Teller and X-ray diffraction. 1H nuclear magnetic resonance spectroscopy was used to characterize the MAA–βCD and BPA–MAA–βCD complex. Several parameters influencing the adsorption efficiency of BPA such as adsorbent dosage, pH of sample solution, contact time, initial concentrations and temperature as well as selectivity and reusability study have been evaluated. MMIP MAA–βCD